Magnetic switch structured triboelectric nanogenerator for continuous and regular harvesting of wind energy. (May 2021) - Liu, Shiming; Li, Xiang; Wang, Yuqi; Yang, Yanfei; Meng, Lixia; Cheng, Tinghai; Wang, Zhong Lin
Abstract: From the extensive research on wind energy harvesting, the triboelectric nanogenerator (TENG) has proven to be effective in converting mechanical energy into electric energy. To supply continuous and regular electric energy above the critical speed, we developed a magnetic switch structured triboelectric nanogenerator (MS-TENG) consisting of transmission gears, energy modulation modules, and a generation unit. When wind falls intermittently on the wind scoop, the energy stored and released by the energy modulation modules at any time does not depend on wind speed but on the magnetic force of the magnets, enabling the wind energy to be converted into continuous and regular electric energy. The experimental results demonstrate that the MS-TENG can operate as a power supply, producing output characteristics of 410 V, 18 μA, 155 nC, and a peak power of 4.82 mW, sufficient to power 500 LEDs in series or a thermometer. Its prospects in the field of wind energy harvesting appear excellent. Graphical Abstract: ga1 Highlights: Magnetic switch structured triboelectric nanogenerator for continuous and regular harvesting of wind energy. When the input speed exceeds the critical speed, the MS-TENG outputs a continuous and regular supply of electric energy. The MS-TENG powered 500 LEDs in series and a thermometer, proving its excellent application prospects.